Use of Brachionus plicatilis (müller, 1786) in the feeding of larvae of the shrimp Litopenaeus vannamei (Boone, 1931) - Silva, Albérico dos Santos; Brito, Luis Otavio; Costa, Wanessa de Melo; Vasconcelos, Rebeca Ferreira Lemos; Galvez, Alfredo Olivera (Arquivos de Ciências do Mar, 2011)
This study aimed to evaluate the effect of substitution of Artemia sp. for rotifer Brachionus plicatilis feed marine shrimp post-larvae of Litopenaeus vannamei in laboratory. The experiment was randomized block, tested four diets with three replicates per treatment. The following treatments were: T1-100% B. plicatilis (30 rotifers.mL- ¹), T2 - 100% inert diet (30% biomass), T3 - 50% of Artemia sp. (5 nauplii.mL- ¹) + 50% B. plicatilis (30 rotifers.mL- ¹) and T4 - 50% of Artemia sp. (5 nauplii.mL- ¹) + 50% inert diet (30% biomass). The results showed no significant difference between T2 and T3. However the T4 treatment was better than the previous ones. Total replacement for rotifers resulted in a mortality of 68.5% of larvae stocked, but the partial use of 50% of Artemia sp. + 50% inert diet was acceptable, not showing then, significant losses in terms of survival and weight of post-larvae.